A comparative analysis of the security of mineral tenure in Zimbabwe under the 'Mines and Minerals Act (21:05)' and the 'Mines and Minerals Amendment Bill 2018' - Gerber, Leonardus J. (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.